Synthesis, characterization and optical spectroscopy of GdPO4:Er3+. (28th April 2020) - Ben Amar, Nozha; Kallel, Tarak; Koubaa, Tarak; Hassairi, Mohamed Amine; Dammak, Mohamed; Cavalli, Enrico
Abstract: A series of Er 3+ ‐doped GdPO4 phosphors was synthesized using a conventional solid‐state reaction. The monazite structure (space group P121 /n1 ) of the obtained materials was confirmed using X‐ray diffraction and Fourier transform infrared spectroscopy. Their optical spectra (excitation, emission, absorption, decay curves) were measured at room temperature in the visible and near‐infrared (NIR) regions. The UV–visible–NIR optical absorption spectrum of GdPO4 :7% Er 3+ was analyzed based on Judd–Ofelt (J–O) theory and the J–O intensity parameter (Ω2, Ω4, Ω6 ) was calculated. J–O intensity parameters were used to evaluate spontaneous emission properties such as branching ratios, transition probabilities, and radiative lifetime. The calculated quantum efficiency of the 1.5 μm emission ( 4 I13/2 − 4 I15/2 ) was calculated to be 89%. This result proved that GdPO4 :Er 3+ is suitable for use in optical amplifiers and is a potential host for laser applications. The most interesting transitions, located at about 540 nm, and 1.0 and 1.5 μm were investigated as a function of doping level and of temperature, to assess the conditions needed for the highest emission performance and to explore the range of application, in particular in the fields of lighting, thermal sensing, and of phosphors for bio‐imaging.